Changing times and agrarian unrest in the Philippines, a social history of LandLordism in Nueva Ecija during the pre-war era, 1909-1941 - Santiago, Fernando A. Jr
In The Huk Rebellion: A study of Peasant Revolt in the Philippines, Benedict J. Kerkvliet attributed agrarian unrest in the 1930s to the breakdown of paternal relations between landlords ant tenants. This historical study shows that such unrest was cause not merely by the deterioration of paternalism but by inherent evils of the landlord-tenant relationship itself. This dissertation is an evaluation of landlordism in Nueva Ecijia from 1909 to 1941. It asserts that the kasama system, on which landlordism in the province was rooted, promoted social inequity, dependence, infringement of basic liberties, insecurity and indebtednes - the inherent evils. It also recognizes the impact of external pressures such as economic forces - general economic instability, consumerism and price control; political and social forces - open government support for peasants, class consciousness, labor leaders, exploitation and ignorance of the law; and acts of nature on the already volatile situation. Many of these pressures were the result of the introduction of liberal democracy, American values and capitalism which redefined the cultural, ethical, intellectual and political climate of the Philippines. It was therefore argued that the confluence of the inherent evils and external pressures led to the breakdown of landlord and tenant relations. The Kasama' system may thus be regarded as a casualty of changing times. For context,the conditions that shaped landlordism in Nueva Ecija were explained. Actual cases of unrest in the province, the extent of unrest, location and the owners of the concerned estates were identified. A survey of the laws that were passed in connection with the tenancy front of the Social Justice Program also shed light on how the Commonwealth government addressed the problems in the countryside.